Medical misinformation: A need for focused designs - Mahad Mirza Baig; Ojla, Muhammad Shah Mureed; Siddiqui, Anas Ali (Journal of the Pakistan Medical Association, 2023)
Respected Editor, The latest coronavirus pandemic has brought the issue of medical misinformation to the forefront of global scientific discussion. Spurred by this interest, many studies have been released to assess knowledge and awareness surrounding COVID-19. This is especially important in our country, Pakistan, where there is a relatively low literacy level and a weakened healthcare infrastructure.1 The prevalence of misinformation and myths among the public easily leads to the stigmatization of victims, increased rates of complications, and higher transmission rates. This phenomenon was observed worldwide through studies which polled participants regarding their understanding and beliefs surrounding COVID-19. After all, it is reasonable to conclude that an individual with the misconception that medical masks are sufficient without social distancing can contribute to transmission rates through ill-advised behaviors.2 Some studies have measured COVID-19 related knowledge in medical students and allied health students respectively, but no studies which we could locate compared the rates of misinformation between medical, allied health, and non-medical students overall.3 Similarly, many studies have attempted to survey the population for commonly held myths related to various illnesses even beyond COVID-19 among the public,4 however; very few have introduced a variable against which to compare correlations. Therefore, the prevalence of misinformation is practically established by the current literature. On the other hand, the cause of misinformation has seldom been explored. To start, more correlation studies may be undertaken with purposeful selection of groups to unearth possible trends in relation to each other. For example, a survey which assesses the prevalence of misinformation among medical and allied health students should also include non-medical students. Such a design would better elucidate whether a trend in the prevalence of misinformation exists, compared to the level of medically-related education. In this hypothetical model, one would expect medical students and allied health students to exhibit lower rates of medical misinformation compared to non-medical students in accordance with the hypothesis that a lack of medical knowledge may contribute to medical misinformation. More purposeful study designs would enable us to breach the current limits of our understanding of medical misinformation and thereby reduce the proliferation of social stigmas, morbidity, and transmission of multiple illnesses. Such studies would enable the proprietors of medical information and health-outreach initiatives to become better guided in their effort to spread helpful information among the public.